Luther’s contribution as bible translator to the German language - Lobenstein-Reichmann, Anja (The Bible translator, 2022)
Translation has often been the primary cultural medium through which history’s greatest visions for society have been communicated and acculturated. But few translations have had as much influence on German religion, politics, culture, and language as Luther’s Bible translation did. This article discusses Luther’s role as a reformer of language and as a Bible translator. Of course these two roles can scarcely be considered independently of each other. The Reformation was deeply marked by his translation choices, and his distinctive way of reading, interpreting, and communicating the Bible’s meaning.
Keywords: Bibel; Reformation; Übersetzung; Luther, Martin